1985
DOI: 10.2320/matertrans1960.26.271
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Hardening of Cu–Al–Ti Alloys by Internal Oxidation

Abstract: alloys internally oxidized over the temperature range 1073-1323K were investigated by X-ray diffractometry, optical and electron microscopy and microvickers hardness testing.identified in internally oxidized Cu-Al alloys and rutile and anatase type TiO2 ininternally oxidized CuTi alloys. In internally oxidized Cu-Al-Ti alloys, all of the oxides observed in the both above Cu-Al and Cu-Ti systems were identified, and no other complex oxides were detected.By electron microscopy, it was revealed that the particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Although the positive role of Ti doping in Cu‐Al 2 O 3 composites is confirmed previously, [ 14,23 ] the mechanisms are still poor. Recent studies by TEM characterization with high resolution and density functional calculations reveal the formation complex oxides and the modification of matrix/particle interfacial energy.…”
Section: Discussion and Outlookmentioning
confidence: 79%
“…Although the positive role of Ti doping in Cu‐Al 2 O 3 composites is confirmed previously, [ 14,23 ] the mechanisms are still poor. Recent studies by TEM characterization with high resolution and density functional calculations reveal the formation complex oxides and the modification of matrix/particle interfacial energy.…”
Section: Discussion and Outlookmentioning
confidence: 79%
“…Many large particles at Cu grain boundaries and numerous fine particles inside the Cu grains were precipitated. The distribution of the fine oxide particles in internally oxidized Cu-Zr alloys differed from that in internally oxidized CuAl-Ti alloys (1), that is, non-uniform precipitation inside the Cu grains occurred, as shown with arrows in Fig. 5.…”
Section: Identificationmentioning
confidence: 99%
“…Especially it was reported that the mixture of Ti oxide with Al 2 O 3 show the possibility of decreasing oxide particle size in copper matrix 14 15 introducing mixture of various oxide in copper matrix. However it has been known as difficult to obtain uniform distribution of the particles 16 17 . For example, it was reported that solid-state mixtures of Ti with Al 2 O 3 might decrease the oxide particle sizes in a copper matrix 17 .…”
mentioning
confidence: 99%
“…However it has been known as difficult to obtain uniform distribution of the particles 16 17 . For example, it was reported that solid-state mixtures of Ti with Al 2 O 3 might decrease the oxide particle sizes in a copper matrix 17 . Differently from the previous work the key step we made in this study was to oxidize Al at high temperature (T = 980 °C) via an internal oxidation process and to control the interface energies between the oxides and the Cu matrix with extra-doped Ti.…”
mentioning
confidence: 99%